Eid Al-Fitr Preserves The Relations of Muslim and Klungkung Royal Palace - Ramdhani, Fajri Zulia (FITK UIN Walisongo, 2024)
Eid al-Fitr is a joyous Muslim holiday celebrated after one month of Ramadan, and this celebration extends to the region of Klungkung, Bali. Puri Agung Klungkung, currently led by Ida Dalem Semaraputra (the King of Klungkung), welcomes visits from Muslims during the Halal bi Halal moment of Eid al-Fitr. This article aims to elucidate the contemporary relationship between Muslims and Puri Agung Klungkung, along with its historical context dating back to the 14th century. The research methodology employed in this article includes field research, incorporating direct observations and in-depth interviews with religious leaders in Klungkung. Furthermore, this study scrutinized various documents and historical evidence concerning the relations between Muslims and the Klungkung Royal Palace. This paper concludes that the association between Puri Agung Klungkung began with the arrival of 40 bodyguards from Dalem Ketut Ngelesir (1380-1460) during their visit to Majapahit, and the subsequent grant of customary land to the east of Puri, which was in Gelgel at that time. Eid al-Fitr celebrations in Klungkung encompass a series of events, including Ramadan Safari, Takbir Keliling, Eid al-Fitr Prayer, Open House, and Halal bi Halal. These activities with Puri Agung Klungkung represent efforts to reinforce longstanding relationships.